2016
DOI: 10.1021/acsnano.6b04471
|View full text |Cite
|
Sign up to set email alerts
|

Davydov Splitting and Excitonic Resonance Effects in Raman Spectra of Few-Layer MoSe2

Abstract: Raman spectra of few-layer MoSe2 were measured with 8 excitation energies. New peaks that appear only near resonance with various exciton states are analyzed, and the modes are assigned.The resonance profiles of the Raman peaks reflect the joint density of states for optical transitions, but the symmetry of the exciton wave functions leads to selective enhancement of the A1g mode at the A exciton energy and the shear mode at the C exciton energy. We also find Davydov splitting of intra-layer A1g, E1g, and A2u … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
130
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(157 citation statements)
references
References 53 publications
23
130
0
Order By: Relevance
“…These two modes increase very rapidly at the beginning of compression, and then the increase is gradually slowed down after 17 GPa. The B 1u mode is often explained as the Davydov pair of the A 1g mode . Our results demonstrated that the B 1u peak appears on the high‐wavenumber side of the A 1g mode at 0 GPa, consistent with the literature, but contrary with .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…These two modes increase very rapidly at the beginning of compression, and then the increase is gradually slowed down after 17 GPa. The B 1u mode is often explained as the Davydov pair of the A 1g mode . Our results demonstrated that the B 1u peak appears on the high‐wavenumber side of the A 1g mode at 0 GPa, consistent with the literature, but contrary with .…”
Section: Resultssupporting
confidence: 86%
“…The B 1u mode is often explained as the Davydov pair of the A 1g mode. [29,30] Our results demonstrated that the B 1u peak appears on the high-wavenumber side of the A 1g mode at 0 GPa, consistent with the literature, [23] but contrary with. [24] The details of B 1u in two samples at 0 GPa can be found in Fig.…”
Section: Effect Of Pressure On Resonant Raman Spectrasupporting
confidence: 84%
“…The variation in the E 2g 1 mode arises from the dielectric screening of the long-range Coulomb interaction and the surface effects. [29] Note that the absence of additional peaks on the low-frequency side of the A 1g mode, which is assigned to the Davydov splitting, [30] as well as the absence of any sharp peak at ≈353 cm −1 , which is related to the interlayer interactions, confirms that the MoSe 2 layers obtained in our experiments are mostly mono-and bilayers.…”
supporting
confidence: 74%
“…Figure f demonstrates the Raman spectrum obtained from the MoSe 2 layers, indicating that the fingerprints of MoSe 2 (A 1g , E 2g , and B 2g phonon modes) are identified. The three discernible Raman features containing 1) the presence of B 2g modes, 2) the intensity ratio of the A 1g to E 2g modes (≈5), and 3) an asymmetric line shape in the A 1g modes, as presented in close inspection of the A 1g mode in Figure f, correlated well with evidence for Davydov splitting, suggesting the synthesis of multilayer MoSe 2 . The sulfide‐based TMD layered materials exhibit strong in‐plane phonon mode intensity, whereas the selenide‐based materials usually possess relatively weak in‐plane phonon modes, in good agreement with earlier studies .…”
mentioning
confidence: 60%